THE IMPACT OF REGIONAL ECONOMIC INTEGRATION ON THE FINANCIAL PERFORMANCE OF MULTINATIONAL COMPANIES - Siska Yuli Anita (INTERNATIONAL JOURNAL OF SOCIETY REVIEWS, 2026)
Regional economic integration, which includes free trade agreements, economic unions, and currency unions, has a positive impact on the financial performance of multinational companies. The study conducted in this research uses qualitative research methods. The results show that regional economic integration creates various opportunities that, if handled properly, can strengthen the financial performance of multinational companies. By utilizing broader market access, more efficient resources, and a more harmonious business environment, companies can improve their competitiveness and profitability.